Corporate Social Responsibility In Indian Hospitality: Hotels In New Delhi (PUSA Journal of Hospitality and Applied Sciences, 2018)
Background: Corporate Social Responsibility (CSR) refers to that part of business activities of an  organization that have a positive impact on the society, environment and their surroundings at large.  The concept of CSR is decade’s old but gained importance in 1990’s after the government made it  mandatory for the organizations to contribute a part of their earnings to the society’s benefit. CSR in  the Indian hospitality also gained importance at the same time when they realized that their customers,  whether foreign or domestic are very much inclined to serve society in certain ways possible. They  realized that people now-a-days do not just buy a product, they take up an initiative of the betterment  of society as well and this motivates the Indian Hospitality to diversify the range and reach of their  CSR initiatives and be called as ‘Socially Responsible Hospitality or Hotel Brand.’ Objective: The  present study is done to understand CSR in terms of hospitality sector, to gain knowledge about  CSR Initiatives taken up in the Hospitality sector: Hotels, and to know the awareness level of the  employees for CSR activities working in perspective Hotels. Methodology: The details of the CSR  Initiatives taken by the perspective hotels were taken by means of interview of the HR personnel of  the organizations, Articles, Magazines, Previous Researches, Websites and Books. Questionnaires  were filled up by the employees working in the organizations to check the employee awareness level  regarding the CSR Initiatives taken up by their organization. Results: Details of the CSR Initiatives  taken up by The Oberoi Maidens, ITC Maurya and The Leela Palace were arrived which indicated  the members of CSR Committee of the hotel, initiatives taken up and their reach, target sectors of  the initiatives and the budgetary support for the CSR Initiatives. Also, the awareness level of the  employees was analyzed and summarized. Conclusion: CSR Initiatives, though a part of the hotel  industry, need to be emphasized more as there is a misconception that the CSR Initiatives are taken  by the hospitality industry for the publicity of their business.
Keywords: Corporate Social Responsibility; Initiatives; Awareness; Contribution